PERENCANAAN CHARGER CONTROLLER DAN BATERAI PADA PROTOTYPE PLTB SKALA KECIL DI TEKNIK LISTRIK POLINEMA - Wijaya Kusuma; Anang Dasa Novfowan (Politeknik Negeri Malang, 2020)
One of the efforts to tackle the energy crisis is by reducing dependence on fossil energy sources and utilizing alternative energy. One of the alternative energy is wind energy. Wind energy can be used to make power plants. Wind power plant is a method to generate electrical energy by turning the wind turbine which connected to the generator, then the electrical energy which generated by generator used for supplying the load. However, the availability of the wind energy are not always constant in strength, thus to make this power plant work continuously to supplying the load it needed the element of electrical energy storage,that is battery.In order to make the electrical energy storage become efficient then used the component to support the battery charging, the presence of these component the energy produced can be stored optimallyand the battery life can be longer. The purpose of this study is to design and analyze the performance of the charger controller and battery in the PLTB system which is then used to support the work of the Wind Power Plant prototype system in State Polytechnic of Malang. The result of this study is how to choose the charger controller and battery based on some consideration, the characteristics of each components before and after be assembled in Wind Power Plant prototype system in State Polytechnic of Malang